The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1002/(sici)1521-186x(200004)21:3<167::aid-bem3>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Inter-laboratory comparison of numerical dosimetry for human exposure to 60 Hz electric and magnetic fields

Abstract: In recent years, with the availability of high resolution models of the human body, numerical computations of induced electric fields and currents have been made in more than one laboratory for various exposure conditions. Despite the verification of computational methods, questions are often asked about the reliability of these data. In this paper, computati onal results from two laboratories that presented data in compatible formats are compared, supplemented with additional data from the third laboratory. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…A key point is that each local vector can be easily obtained from the global vector through a linear restriction operator of matrix (2) In the same way, a linear prolongation operator of matrix allows to obtain the global contribution which correspond to each local vector, so that (3) In the case of matching meshes, is a permutation of the matrix , and it can be shown that is simply the transposed matrix of . In the general case of non-matching meshes, each term of the local vector is computed from the global one by using a first-order finite-element interpolation.…”
Section: A Restriction/prolongation Operatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…A key point is that each local vector can be easily obtained from the global vector through a linear restriction operator of matrix (2) In the same way, a linear prolongation operator of matrix allows to obtain the global contribution which correspond to each local vector, so that (3) In the case of matching meshes, is a permutation of the matrix , and it can be shown that is simply the transposed matrix of . In the general case of non-matching meshes, each term of the local vector is computed from the global one by using a first-order finite-element interpolation.…”
Section: A Restriction/prolongation Operatorsmentioning
confidence: 99%
“…Utah) [3], Univ. Victoria [3], [18], Brook Air Force [18], ZOL [19]) and methods (IM, SPFD Scalar Potential FD TDFD Time Domain FD, FEM).…”
Section: Comparison With Available Datamentioning
confidence: 99%
See 2 more Smart Citations
“…We simulated the exposure of the human body to a 60 Hz, uniform 1 mT back-to-front magnetic field, and compared the results with the values found in literature [3], [18], [19]. The computational phantom is based on the Visible Human (see Fig.…”
Section: Comparison With Available Datamentioning
confidence: 99%